Cost-efficient forest management for safeguarding Siberian flying squirrel (Pteromys volans) habitats in Central Finland - Ahtikoski, Anssi; Nikula, Ari; Nivala, Vesa; Haikarainen, Soili; Juutinen, Artti (Taylor & Francis, 2023)
Protection of vulnerable species often creates conflicts between land use and conservation management. Particularly challenging is the case of Siberian flying squirrel (SFS; Pteromys volans). SFS favours mature forest habitats, which are often the target for logging, and therefore its protection causes opportunity costs. In our analysis a regional case study was applied as a platform to create alternative forest management scenarios. These scenarios aimed to maintain and improve SFS habitats with varying magnitudes, from no action in SFS habitat improvement to increasing the amount of suitable habitat for SFS. Stand projections for each forest management scenario were modelled with the Motti stand simulator, and the simulated stand structures were further analyzed using specific indexes with Geographic Information System (GIS) methodologies and tools to predict potential nesting and feeding habitats and connectivity for SFS. Connectivity between habitats was assessed with a Least Cost Path analysis. The results showed that some forest management scenarios were more cost-efficient than others in maintaining habitat suitability and connectivity for SFS. Further, with adjusted cutting removals (due to restrictions other than SFS habitat related, mainly recreation) an additional hectare suitable for SFS habitat was considerably more cost-efficient than without the adjustment.
Keywords: Siberian flying squirrel; cost-effectiveness; simulation; conservation